Pengaruh Digitalisasi Terhadap Adopsi Teknologi UMKM Dalam Menggunakan Alat Pembayaran QRIS (Quick Response Code Indonesia Standard) - Widyayanti, Evi Rosalina; Insiatiningsih, Insiatiningsih (Program Studi Manajemen Fakultas Ekonomi UST, 2024)
The aim of this research is to determine the influence of digitalization which is fast, practical, effective and safe to what extent it influences the adoption of QRIS technology for MSMEs. The research was conducted in the Special Region of Yogyakarta with MSME respondents using QRIS (Quick Response Code Indonesia Standard). The background of this research is the increasing importance of financial technology for all elements of society, including MSMEs and customers who are increasingly comfortable using digital payments. The research methodology used is a quantitative approach with a research model referring to the application of TAM (Technology Acceptance Model). The analytical tool used is Smart PLS-SEM. The data used was obtained through distributing questionnaires to MSMEs using QRIS in DIY via Google form. The variables used were Digitalization, Perceived Usefulness, Perceived Ease of Use, Attitude, Behavioral Intention and Actual Usage. With the results of the first analysis, digitalization has an insignificant positive effect on perceived usefulness. Second, digitalization has a significant positive effect on perceived ease of use. Third, perceived ease of use has a significant positive effect on perceived usefulness. The four perceived usefulness have a significant positive effect on attitude. Fifth, perceived ease of use has an insignificant positive effect on attitude. Sixth, attitude has a significant positive effect on behavioral intention and finally behavioral intention has a significant positive effect on actual usage.